Why stop at two opinions?: reply to McCrae (2020) - Bleidorn, Wiebke; Hill, Patrick L.; Back, Mitja D.; Denissen, Jaap J. A.; Hennecke, Marie; Hopwood, Christopher J.; Jokela, Markus; Kandler, Christian; Lucas, Richard E.; Luhmann, Maike; Orth, Ulrich; Wagner, Jenny; et al. (The American psychologist, 2020)
McCrae (2020) argues that it is premature to explore interventions focused on personality change. In his commentary, he suggests that interventions should be promoted only if their effects in self-report data are confirmed by the additional opinion of informants. We agree with the essence of his position and would go further by envisioning a new framework for rigorous collaborative research on personality change (Bleidorn et al., 2020). We nevertheless maintain that policymakers would benefit from considering the additional opinion of personality scientists. (PsycInfo Database Record (c) 2020 APA, all rights reserved).
Gesehen am 08.09.2020